Adenoviral-mediated gene expression of hepatocyte growth factor prevents postoperative peritoneal adhesion in a rat model - Liu, Hong-Jun; Wu, Chu-Tse; Duan, Hai-Feng; Wu, Bin; Lu, Zhuo-Zhuang; Wang, Lisheng (Surgery, 2006)
Mesothelial cell proliferation and migration play important roles in reducing formation of postoperative peritoneal adhesions. Hepatocyte growth factor (HGF) is a multifunctional cytokine that stimulates proliferation and migration of various cell types, including mesothelial cells. We investigated the effect of adenovirus-mediated HGF gene expression on the proliferation and migration of mesothelial cells and evaluated its preventive effects on postoperative formation of peritoneal adhesions. Rat mesothelial cells were isolated and characterized by expression of cytokeratin and vimentin. Immunohistochemical staining showed that these cells expressed c-Met, the receptor for HGF. Adenoviral-mediated HGF gene transfer into mesothelial cells resulted in high expression of HGF and enhanced migration. To evaluate the preventive effects of adenoviral-mediated HGF gene transfer on the formation of postoperative peritoneal adhesion, we employed a rat model of cecum abrasion-induced adhesion formation in which 80% of the rats developed postoperative peritoneal adhesions. Local application of recombinant adenovirus carrying the HGF gene reduced adhesion formation in 16 of 20 control rats compared with 7 of 20 treated rats in this model. These results suggest that adenoviral-mediated HGF gene transfer may be a novel strategy for preventing postoperative peritoneal adhesions.